2009
DOI: 10.1111/j.1600-0609.2009.01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combination therapy of hydroxyurea with l‐carnitine and magnesium chloride on hematologic parameters and cardiac function of patients with β‐thalassemia intermedia

Abstract: Combination of hydroxyurea with l-carnitine or magnesium could be more effective in improving hematologic parameters and cardiac status in patients with beta-thalassemia intermedia than hydroxyurea alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
2
11
0
1
Order By: Relevance
“…Magnesium has demonstrated beneficial effects on hematological parameters in the present study and other work through its powerful antioxidant properties [50]. Indeed, magnesium reduces the load of free radicals and has potency in inhibiting platelet aggregation [51] which gives this oligo-element a powerful protective effect against the blood toxicity of CCl 4 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Magnesium has demonstrated beneficial effects on hematological parameters in the present study and other work through its powerful antioxidant properties [50]. Indeed, magnesium reduces the load of free radicals and has potency in inhibiting platelet aggregation [51] which gives this oligo-element a powerful protective effect against the blood toxicity of CCl 4 .…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, magnesium reduces the load of free radicals and has potency in inhibiting platelet aggregation [51] which gives this oligo-element a powerful protective effect against the blood toxicity of CCl 4 . Magnesium also has the power to protect blood from vanadate toxicity [12] and stabilize damaged red blood cell membranes [50]. In mouse, oral magnesium supplementation was found to increase hemoglobin levels and to reduce erythrocyte dehydration [52].…”
Section: Discussionmentioning
confidence: 99%
“…A beneficial role in patients with pulmonary hypertension was suggested, especially upon combination with the antioxidant L-carnitine, although these findings primarily relied on echocardiographic findings. 66,99,100 In smaller studies, hydroxyurea therapy was also associated with improvements in endocrine function, 80 leg ulcers, 101 and extramedullary hemtopoietic tumors. 102 These findings are further confirmed through a 2010 cross-sectional study of 584 b-thalassemia intermedia patients from the Middle East and Italy, where hydroxyurea therapy was associated with reduced adjusted odds of extramedullary hemtopoietic tumors (0.52, 95% CI, 0.30-0.91), pulmonary hypertension (0.42, 95% CI, 0.20-0.90), leg ulcers (0.10, 95% CI, 0.02-0.43), hypothyroidism (0.05, 95% CI, 0.01-0.45), and osteoporosis (0.02, 95% CI, 0.01-0.09).…”
Section: Other Clinical Outcomesmentioning
confidence: 99%
“…In patients who were not transfused, the Hb concentration increased. The same Iranian group more recently showed that the combination of hydroxyurea with L-carnitine or magnesium could be more effective in improving haematologic parameters and cardiac status in patients with TI than hydroxyurea alone (Karimi et al, 2010). However, whether hydroxycarbamide therapy can prevent rather than treat cardiac complication including PHT is not yet evaluated.…”
Section: Modulation Of Fetal Haemoglobin Productionmentioning
confidence: 99%